Visible-light mediated C-3 amination of quinoxalin-2(1H)-ones via electron donor-acceptor complexation - More, Devidas A.; Gayathri, P. R.; Thete, Kishor R.; Muthukrishnan, M. (Asian Journal of Organic Chemistry, 2024)
The formation of carbon-nitrogen bonds holds paramount importance in the realm of synthetic organic chemistry, finding extensive applications in the synthesis of pharmaceuticals, agrochemicals, and organic materials. Herein, we describe a novel EDA complex mediated, metal- and photocatalyst-free, visible-light-initiated direct C-3 amination of biologically important, quinoxalin-2(1H)-one moiety. The key to the success lies in the formation of a photoactivated electron donor-acceptor complex between quinoxalin-2(1H)-one and amine, which undergo subsequent electron transfer reaction to effect the desired transformation. A diverse array of 3-aminoquinoxalin-2(1H)-ones were prepared employing this process and the yields are up to 87%. This work represents a significant advancement toward a more environmentally friendly and efficient approach, characterized by mild reaction conditions and a high atom economy.
Keywords: C-3 amination; Dehydrogenative amination; EDA complex; quinoxalin-2(1H)-ones